Military Engineering - Dekoulis, George (IntechOpen, 2020)
This book, "Military Engineering", is a collection of reviewed and relevant research chapters, offering a comprehensive overview of the recent developments in the field of military engineering. The book comprises single chapters authored by various researchers and edited by an expert active in the physical sciences, engineering and technology research area. All chapters are complete in themselves but united under a common research study topic. This publication aims at providing a thorough overview of the latest research efforts by international authors on military engineering, and opening new possible research paths for further novel developments.